Revisiting the usage of Islamic credit card in the light of Maqasid Shariah / Ammar Fadzil Shuhaimi - Shuhaimi, Ammar Fadzil (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
The Islamic financial institution in Malaysia has been developed since 48 years which is started from 1970. The existence of various instruments that has many benefits and facilities in Islamic financial system has made the Islamic products competitive with the conventional products. One of the products that attract people to Islamic financial institution is the credit card that is based on Islamic principles. However, nowadays the usage of Islamic credit card seems to bring disadvantage to the youth which they use the credit card not accordance to Maqasid Syariah. So, the preservation of five basis of Maqasid Syariah is not achieved is this current situation. This study aims to evaluate the usage of Islamic credit card in perspective of Maqasid Syariah especially in protecting the wealth and also explain the usage of Islamic credit card which focuses on preservation of religion, life, intellect, lineage and property. Therefore, this research is done by interviewing Mr. Mahyuddin Khalid that involves in using Islamic credit card in Bank Islam Malaysia Berhad (BIMB). The findings from this study is the current Islamic credit card is not in line with the framework of Maqasid Syariah due to individual’s behavior and also few problems faced by Islamic financial institution in Malaysia for example, Bank Islam Malaysia Berhad (BIMB) which is one of the institution that provides Islamic credit card.